Learning of Animals Based on Mobile Applications Augmented Reality at SD Bintara I - Wahyu Aji Nugroho; Adam Arif Budiman (Journal TIFDA (Technology Information and Data Analytic), 2025)
The problem with teaching young children to recognize animals in English is the lack of interactive media that is interesting and easy to understand, which results in low interest and comprehension among children. This study aims to develop an interactive learning application based on Augmented Reality (AR) to help children recognize animals in English in a visual and fun way. The development method used is the Prototype method with stages of needs analysis, design, implementation, and testing. This application was built using Unity, Vuforia SDK, and the C# programming language, and displays 3D animal objects that are scanned through markers accompanied by voice pronunciation in English. Testing results from 15 respondents indicate that the application is easy to use, engaging, and effective in increasing children's interest in learning. Therefore, this AR application is suitable for use as an interactive learning medium for introducing animals in English.